The Impact of Victim Blaming on Social Media and Handling Efforts for Victims of Sexual Violence - Ubino, Sity Nurhaliza; Astuti, Kamsih (LifeSciFi, 2025)
Victim blaming is a persistent legal and social problem in cases of sexual violence, particularly on social media, where victims are often judged and blamed for their clothing, behavior, or background. Such responses not only reflect gender stereotypes and patriarchal norms but also hinder justice and support for survivors. This study aims to examine the forms of victim blaming on digital platforms, its legal and social implications, and strategies to address it. Using a literature review method, sources from psychology, media studies, law, and socio-cultural perspectives were analyzed. The findings indicate that victim blaming is fueled by media bias, entrenched gender norms, patriarchal culture, and low public digital literacy. Its consequences include severe psychological trauma, social isolation, and reluctance to pursue legal action or professional assistance. The study concludes that a comprehensive, cross-sectoral approach encompassing public education, media reform, stronger legal protections, and empathetic psychological support is essential to creating a safer, more just, and victim-centered digital environment. Such synergy between legal, psychological, and social sectors is necessary to break the cycle of secondary victimization and promote justice for survivors.